Post-selection and return of foraged material by Acromyrmex subterraneus brunneus (Hymenoptera: Formicidae) - Camargo, Roberto S. [UNESP]; Forti, Luiz Carlos [UNESP]; Matos, Carlos Alberto O. de [UNESP]; Lopes, Juliane F. [UNESP]; Andrade, Ana Paula P. de [UNESP]; Ramos, Vânia M. [UNESP] (My University, 2003)
Two colonies of Acromyrmex subterraneus brunneus Forel (Hymenoptera: Formicidae) were studied regarding their behavior during cultivation of the fungus garden to determine a) the existence of post-selection of foraged material by the workers, and b) if present, the mechanism of this discrimination and how this material is returned. Many studies on plant processing by leaf-cutting ants have been carried out, but none of them has investigated the decision-making process of workers in the case of erroneous food selection. For this purpose, material with different degrees of moisture and hardness (floral sponge, polystyrene, plastic and clay) were individually offered to the colonies and the tasks performed by the different size categories were carefully recorded. Three tasks, i.e., foraging, cultivation of the fungus garden and return of the foraged material, were studied and subdivided into 14 subtasks. Analysis of all inert materials as a whole showed the presence of post-selection of foraged material through the return of material inadequate for the workers and the fungus. Discrimination of the inert material was observed at the time of shredding, probably based on parameters such as physical resistance to cutting and moisture content. A. s. brunneus workers showed flexibility in their activities during substrate processing. The observed post-selection of foraged material provides strong evidence for the cognitive abilities of worker ants and of the colony as a whole. Polymorphism and a complex society represent vital characteristics for the ecological success of this species.
Keywords: Acromyrmex subterraneus brunneus; Inert material; Leaf-cutting ant; Subtask; Task; Acromyrmex; Acromyrmex subterraneus; Atta; Formicidae; Fungi; Hymenoptera